Disorder and order in unfolded and disordered peptides and proteins: A view derived from tripeptide conformational analysis. I. Tripeptides with long and predominantly hydrophobic side chains. Issue 6 (27th February 2013) - Schweitzer‐Stenner, Reinhard; Hagarman, Andrew; Toal, Siobhan; Mathieu, Daniel; Schwalbe, Harald
Abstract: We performed a conformational analysis of the central residues of three tripeptides glycyl‐L ‐isoleucyl‐glycine (GIG), glycyl‐L ‐tyrosyl‐glycine (GYG) and glycyl‐L ‐arginyl‐glycine (GRG) in aqueous solution, based on a global analysis of amide I′ band profiles and NMR J‐coupling constants. The results are compared with recently reported distributions of GVG, GFG and GEG. For GIG and GYG, we found that even though the polyproline II (pPII) fraction is below 0.5, it is still the most populated conformation, whereas GVG and GFG show both a larger β‐strand fraction. For GRG, we observed a clear dominance of pPII over β‐strand, reminiscent of observations for GEG and GKG. This finding indicates that terminal charges on otherwise hydrophobic residue side chains stabilize pPII over β‐strand conformations. For all peptides investigated we found that a variety of compact and turn‐like conformations constitute nearly 20 percent of their conformational distributions. Attempts to analyze our data with a simple two‐state pPII⇔︁β model therefore do not yield any satisfactory reproduction of experimental results. A comparison of the obtained GxG ensembles with conformational distributions of GxG segments in truncated coil libraries (helices and sheets omitted) revealed a much larger fraction of type II β i +2 and type III β like conformations for the latter. Thus, a comparison of conformational distributions of unfolded peptide segments in solution and in coil libraries reveal interesting information on how the interplay between intrinsic propensities of amino acid residues and non‐local interactions in polypeptide chains determine the conformations of loop segments in proteins. Proteins 2013; © 2012 Wiley Periodicals, Inc.